Investigação de equilíbrios através de potenciometria e voltametria com resolução multivariada de curvas - Missel, Josué da Rosa (2012)
The interaction between the amino acid glutathione (GSH) and zinc (II) and cadmium (II) ions was investigated using data obtained by potentiometric and voltammetric measurements. Solutions with ionic strength 0.1 M KCl with different metal-ligand ratios were titrated with standard solution of KOH and the pH profiles obtained were used to propose models of chemical equilibrium between the species. The potentiometric data treatment was performed using the Hyperquad software, which enabled that the formation constants of the differents pecies could be refined. The program HySS,belonging to the Hyperquad computer package, was used to obtain the species distribution curves. The best fit models of equilibrium was reached suggesting the existence of species in which the metal ions were coordinated by one and two molecules of the ligand, and the highest values were found for log β complex type MH2L, MHL2 and ML2. For the voltammetric data, multivariate curve resolution with alternating least squares (MCR-ALS) was applied. Several voltammograms recorded at different metal-ligand ratios generated a series of overlapping peaks, from which it was possible to recover the pure voltammograms and their concentration profiles applying non-negativity, unimodality and "closure" as constraints. For both systems studied (GSH-Zn and GSH-Cd), voltammograms were resolved to three components, the free metal and two complexes. The potentiometric and voltammetric data treated with MCR-ALS were capable to complement one another, constituting a important tool in the investigation of chemical equilibria between metal ions and ligands.